Risk management and financial performance: empirical evidence from the Nigerian banking industry - Elisha, Douglas Enahoro (Graduate School of Business (GSB), 2025)
The banking industry is an important sector of any economy because banks are primarily tasked with the intermediation role of channeling funds from the deficit unit to the surplus unit through deposit mobilization and the creation of risk assets (Loans and Advances). This intermediation process is fraught with inherent risks, including credit, operational, liquidity, and solvency risks. In ensuring that banks function efficiently, they are obligated to manage these risks to ensure the creation of value for shareholders and other stakeholders. Risk management is critical to the Nigerian banking industry's system architecture. This dissertation sought to examine the relationship between risk management practices, proxied by its various components, including solvency risk (CAR), liquidity risk (LDR), credit risk (NPL), operational risk, and profitability. The study employed a sample of 12 banks, representing 97.0% of the banking industry's total assets over 11 years, from 2012 to 2022. The random and fixed effect panel technique was employed in estimating the static panel model to examine the impact of risk management on the performance of banks. The regression analysis results indicate a strong adverse effect of credit and operational risks on return on assets, suggesting that higher returns on assets are associated with lower loan loss provisions and operational losses. This indicates the importance of asset quality and risk management practices in banks' delivery of quality financial performance. On the contrary, capital ratio and liquidity risks positively affect returns on assets and equity. The study revealed a negative coefficient for banks' ages and profitability, indicating that older banks tend to have lower profitability, primarily due to Nigeria's rapidly evolving banking landscape, creating discriminating advantages for the new-generation banks. However, ownership type does not exhibit statistically significant coefficients with banks' profitability, suggesting that their direct impact on bank profitability may be limited in the context of the variables considered in the analysis Based on the findings, banks are encouraged to design data-driven policies on the capital adequacy ratios with the twin objectives of meeting the regulatory hurdle of 15% and pursuing loan book expansion. This will support the growth of the overall economy when credits are channeled to the productive sectors of the economy; moreover, expanded loan books will create interest income that ultimately enhances the profitability of banks. The study also demonstrated that banks are susceptible to time decay. Older banks underperform newer banks; therefore, banks must undertake frequent periodic analyses of their processes, strategies, and supporting infrastructure to adapt to the changing environment and landscape. Based on the findings, banks are encouraged to design data-driven policies on the capital adequacy ratios with the twin objectives of meeting the regulatory hurdle of 15% and pursuing loan book expansion. This will support the growth of the overall economy when credits are channeled to the productive sectors of the economy; moreover, expanded loan books will create interest income that ultimately enhances the profitability of banks. The study also demonstrated that banks are susceptible to time decay. Older banks underperform newer banks; therefore, banks must undertake frequent periodic analyses of their processes, strategies, and supporting infrastructure to adapt to the changing environment and landscape.